Entertainment activities and the risk of Alzheimer’s disease: a Mendelian randomization analysis - Lu, Tianqi; Wang, Lilin; Zheng, Yunhua; Liu, Hua; Liu, Jianyu (Frontiers in Aging Neuroscience, 2024)
Background Effective prevention is key to addressing the increasing prevalence and mortality of Alzheimer’s disease. Assessing the causal relationship between modifiable entertainment activity factors and the risk of Alzheimer’s disease is important for developing public health measures, but establishing causal relationships in epidemiological data may be challenging. Methods This study using the two-sample Mendelian randomization analysis aimed to investigate the causal effect of entertainment activity factors on the risk of Alzheimer’s disease. Summary statistics from publicly available genome-wide association studies were used to analyze 14 modifiable entertainment activity. The inverse variance weighted random effects method as the primary analytical method to estimate causal effects was used. Additionally performed MR-Egger, weighted median and weighted model methods to assess the robustness of the results. The reliability of our findings was validated through systematic sensitivity analyses and tests for heterogeneity. Results We found significant correlation between time spent using computer (odds ratio 0.998; 95% confidence interval 0.996–0.999; p = 0.013) and Alzheimer’s disease, compared to other studied entertainment activities that had no significant causal relationship with Alzheimer’s disease. Conclusion Our findings support the hypothesis that increased computer use may reduce the risk of Alzheimer’s disease, providing potential strategic directions for the prevention of neurodegenerative diseases.